Partnership disengagement from primary community care networks (PCCNs): A qualitative study for a national demonstration project - Lin Cheng-Chieh; Liau Chia-Yi; Lin Yung-Kai; Lin Blossom (BMC, 2010)
Abstract Background The Primary Community Care Network (PCCN) Demonstration Project, launched by the Bureau of National Health Insurance (BNHI) in 2003, is still in progress. Partnership structures in PCCNs represent both contractual clinic-to-clinic and clinic-to-hospital member relationships of organizational aspects. The partnership structures are the formal relationships between individuals and the total network. Their organizational design aims to ensure effective communication, coordination, and integration across the total network. Previous studies have focused largely on how contractual integration among the partnerships works and on its effects. Few studies, however, have tried to understand partnership disengagement in PCCNs. This study explores why some partnerships in PCCNs disengage. Methods This study used a qualitative methodology with semi-structured questions for in-depth interviews. The semi-structured questions were pre-designed to explore the factors driving partnership disengagement. Thirty-seven clinic members who had withdrawn from their PCCNs were identified from the 2003-2005 Taiwan Primary Community Care Network Lists. Results Organization/participant factors (extra working time spend and facility competency), network factors (partner collaboration), and community factors (health policy design incompatibility, patient-physician relationship, and effectiveness) are reasons for clinic physicians to withdraw or change their partnerships within the PCCNs. Conclusions To strengthen partnership relationships, several suggestions are made, including to establish clinic and hospital member relationships, and to reduce administrative work. In addition, both educating the public about the concept of family doctors and ensuring well-organized national health policies could help health care providers improve the integration processes.